Unlocking New Business Models: How Blockchain is Shaping Digital Entrepreneurship in Iringa Municipal - Kibona, Lusekelo (International Journal of Applied and Scientific Research, 2024)
This study explored the impact of blockchain technology on digital entrepreneurship in Iringa Municipal, focusing on its potential to unlock new business models, enhance the entrepreneurial ecosystem, and identify challenges and opportunities associated with its adoption. A mixed-method approach was employed, involving a survey of 100 local entrepreneurs, which provided insights into their perceptions and experiences with blockchain. The findings revealed that a significant proportion of respondents viewed blockchain as a catalyst for innovation, with a majority recognizing its potential for market expansion and collaboration. However, challenges such as regulatory barriers, technical constraints, and financial limitations were also identified as impediments to widespread adoption. The study concluded that while blockchain holds promise for transforming the entrepreneurial landscape, concerted efforts are needed to educate stakeholders and create a supportive environment that facilitates its integration. Recommendations were made to enhance awareness, promote collaboration, and develop innovative funding mechanisms to fully leverage the benefits of blockchain technology in driving economic growth and innovation in the region.